Multi-Attribute Analysis Using Coherency and Ant-Tracking Techniques for Fault and Fracture Detection in La Florida Anticline, Llanos Foothills, Colombia - Ziyad Albesher; James Kellogg; Ibraheem Hafiza; Essam Saeid (Geosciences, 2020)
We present techniques to reduce noise and enhance seismic quality, making possible the first multi-attribute analysis of a 3D seismic volume in the Llanos Foothills (La Florida anticline) of Colombia using coherency and ant-tracking techniques for fault and fracture detection. The results could help reduce risk in models of reservoir fracture porosity and permeability. The dominant fracture strike direction in the studied seismic volume (La Florida anticline) is NE–SW (055 ± 20°), parallel to the structural strike of the adjacent Eastern Cordillera Foothills. The application of the ant-tracking technique also reveals the NE-SW fracture set for the reservoir rocks in the La Florida anticline as well as in the non-folded reservoir rocks to the SE. We compared the fracture intensity and orientation in folded rocks with the fracture intensity and orientation in non-folded rocks. Our study showed NE-SW, NW-SE, and E-W fracture orientations in the non-folded seismic volume, suggesting that regional stresses could produce these fracture sets, not just folding processes as previously proposed. The NW-SE and WNW-ESE fracture sets are only found in the Guayabo Formation (11 Ma–Present). A right–lateral strike–slip displacement on the nearby Algeciras fault system in the last 2 m.y. may have generated WNW-ESE and NW-SE Riedel-type shear fractures in the study area.